EFEKTIVITAS PENGGUNAAN MEDIA WAYANG BEBER KREASI TERHADAP KEMAMPUAN BERCERITA SISWA - Arwani, Misbah; Rifa Suci Wulandari (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2022)
This research was conducted to determine the effectiveness use of wayang beber creation media on group B students’ storytelling ability at PAUD Merak Ponorogo in 2020. The research design used was experimental research in the form of Quasi Experimental Design. The data collection techniques used in this study were observation and documentation. The research instruments used were observation and documentation guidelines. To test the research hypothesis, the data analysis technique used was t-test. Before the t-test is carried out, the prerequisite tests were the normality and homogeneity tests. Based on the data analysis test carried out with the help of SPSS 18, the significance value (2-tailed) was 0.001 <0.05, then H0 was rejected and Ha was accepted. The results of testing these data indicated that the use of wayang beber creation media was effective for students' storytelling ability. In related to the research result, teachers are suggested to use wayang beber creation media as one of effective learning tools to increase students’ storytelling ability.